2020
DOI: 10.1080/00958964.2020.1845589
|View full text |Cite
|
Sign up to set email alerts
|

Safe spaces or a pedagogy of discomfort? Senior high-school teachers’ meta-emotion philosophies and climate change education

Abstract: This is an open access article distributed under the terms of the creative commons attribution-noncommercial-noderivatives license (http:// creativecommons.org/licenses/by-nc-nd/4.0/), which permits non-commercial re-use, distribution, and reproduction in any medium, provided the original work is properly cited, and is not altered, transformed, or built upon in any way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…Reasons for picking the first strategy commonly include the focus of national exams on theory, a focus that creates the risk of painting too narrow a picture of sustainability issues [15]. Neglecting or glossing over negative emotions in sustainability debates has been deemed a common and undesirable trait of current science education practice [22]. Exploring teacher-initiated learning aims related to sustainability could further improve our understanding of current EC practice.…”
Section: Current Ec Teaching Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Reasons for picking the first strategy commonly include the focus of national exams on theory, a focus that creates the risk of painting too narrow a picture of sustainability issues [15]. Neglecting or glossing over negative emotions in sustainability debates has been deemed a common and undesirable trait of current science education practice [22]. Exploring teacher-initiated learning aims related to sustainability could further improve our understanding of current EC practice.…”
Section: Current Ec Teaching Practicementioning
confidence: 99%
“…Common with sustainability thinking is a general feeling of hopelessness on the one hand, caused by the idea that it already is too late to turn the tide [22]. On the other hand, people might underestimate sustainability issues because effects of sustainability issues are often not felt close to home, which results in feelings of apathy and resignation [24].…”
Section: Confidence and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Verlie et al, (2020) reported that educators in Eastern Australia commonly feel overwhelmed with profound emotions around climate change. Further complications arise when youth are distrustful of older generations, feeling betrayed by those who, despite decades of warning, have historically proven reticent to take climate action (Natural History Museum, 2021; Jones & Davison, 2021;Ojala, 2021). What little climate change educational youth may have experienced has often left them feeling disempowered (Hickman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the predicted scale of the impact climate change may have on future generations, academic literature relating to youth perceptions and concerns surrounding climate change has been limited (Jones & Davison, 2021;Lee, Gjersoe, O'Neill, & Barnett, 2020). Research documenting the emotional and psychological toll that climate change discourse is having on youth, however, is rapidly increasing (Ojala, 2021;Panu, 2020;Verlie, Clark, Jarrett, & Supriyono, 2020). Formal education has a critical role to play in bringing about the changes needed (Gough, 2015).…”
Section: Introductionmentioning
confidence: 99%